Minimally invasive colorectal cancer surgery in Europe: implementation and outcomes - Babaei, Masoud; Balavarca, Yesilda; Becker, Nikolaus; Ulrich, Alexis; Ulrich, Cornelia; Schrotz-King, Petra; Brenner, Hermann (Medicine, 2016)
Minimally invasive surgery (MIS) of colorectal cancer (CRC) was first introduced over 20 years ago and recently has gained increasing acceptance and usage beyond clinical trials. However, data on dissemination of the method across countries and on long-term outcomes are still sparse. - In the context of a European collaborative study, a total of 112,023 CRC cases from 3 population-based (N = 109,695) and 4 institute-based clinical cancer registries (N = 2328) were studied and compared on the utilization of MIS versus open surgery. Cox regression models were applied to study associations between surgery type and survival of patients from the population-based registries. The study considered adjustment for potential confounders. - The percentage of CRC patients undergoing MIS differed substantially between centers and generally increased over time. MIS was significantly less often used in stage II to IV colon cancer compared with stage I in most centers. MIS tended to be less often used in older (70+) than in younger colon cancer patients. MIS tended to be more often used in women than in men with rectal cancer. MIS was associated with significantly reduced mortality among colon cancer patients in the Netherlands (hazard ratio [HR] 0.66, 95% confidence interval [CI] (0.63-0.69), Sweden (HR 0.68, 95% CI 0.60-0.76), and Norway (HR 0.73, 95% CI 0.67-0.79). Likewise, MIS was associated with reduced mortality of rectal cancer patients in the Netherlands (HR 0.74, 95% CI 0.68-0.80) and Sweden (HR 0.77, 95% CI 0.66-0.90). - Utilization of MIS in CRC resection is increasing, but large variation between European countries and clinical centers prevails. Our results support association of MIS with substantially enhanced survival among colon cancer patients. Further studies controlling for selection bias and residual confounding are needed to establish role of MIS in survival of patients.